2021
DOI: 10.11622/smedj.2021073
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and expansion of newborn screening programmes in Singapore

Abstract: In Singapore, the newborn screening programme was started in 1965 in order to reduce the high neonatal mortality and neurological morbidity owing to severe hyperbilirubinaemia caused by erythrocyte glucose-6-phosphate dehydrogenase deficiency. About 25 years later, the national newborn screening for congenital hypothyroidism was established. Subsequently, universal newborn hearing screening and screening for multiple inborn errors of metabolism using tandem mass spectrometry were introduced as national program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Universal hearing screening and screening for multiple IEMs were introduced as national programs in 2003 and 2006, respectively, with current NBS coverage at almost 100% without a screening law. A comprehensive review of the history of NBS and other screening activities with newborns was published in 2021 and notes the possibility of Singapore becoming a screening laboratory center for other developing programs in the region (e.g., Brunei, Myanmar, Laos, and Cambodia) [ 635 ]. An editorial discussing the history of NBS for CH also was recently published [ 636 ] along with an article advising on some of the issues related to cord blood screening for CH (e.g., mode of newborn delivery and TSH measurement method) [ 637 ].…”
Section: Resultsmentioning
confidence: 99%
“…Universal hearing screening and screening for multiple IEMs were introduced as national programs in 2003 and 2006, respectively, with current NBS coverage at almost 100% without a screening law. A comprehensive review of the history of NBS and other screening activities with newborns was published in 2021 and notes the possibility of Singapore becoming a screening laboratory center for other developing programs in the region (e.g., Brunei, Myanmar, Laos, and Cambodia) [ 635 ]. An editorial discussing the history of NBS for CH also was recently published [ 636 ] along with an article advising on some of the issues related to cord blood screening for CH (e.g., mode of newborn delivery and TSH measurement method) [ 637 ].…”
Section: Resultsmentioning
confidence: 99%
“…10,11 The recent literature in Singapore provided an interesting look into the controversies present in a well-developed nation (ranked eighth in the global health index), which lacks a DDH screening program despite pediatric orthopedists and neonatologists' recommendations. 10,11,16,36 Our study has limitations and some study design flaws. Despite the rigorous and tiered search strategy, no screening program was identified in five countries, representing possible exclusion bias.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent publications comment on individual, institutional progress toward a formal screening process; however, that does not appear nationally. 10 , 11 , 36 Reasons for difficulties encompassed the gap between neonatology clinical screening and orthopedic referral, concerns a typical hip at the time of neonatal screen later develops dysplasia, variations in patient population characteristics, and ongoing debates about the timing of a screening ultrasound. 10 , 11 The recent literature in Singapore provided an interesting look into the controversies present in a well-developed nation (ranked eighth in the global health index), which lacks a DDH screening program despite pediatric orthopedists and neonatologists’ recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous nationwide studies, the prevalence of hearing loss among newborns is significant compared with other disabilities, accounting for 1–3 in every 1,000 newborns [ 1 – 5 ]. According to Mazlan et al [ 3 ], from 2010 to 2019, the prevalence of hearing loss among newborns in Malaysia was comparable to that in the United States [ 5 ] and Singapore [ 2 ]. Data indicated that the median age of deafness diagnosis for children with deaf and hard of hearing (DHH) was approximately 3.8 months.…”
Section: Introductionmentioning
confidence: 99%